Effect of storage periods on the quality and shelf life of beef liver at refrigerated temperature - MS Akhter; H Khatun; MA Hashem; MM Rahman; M Khan (Meat Research, 2022)
The current study investigated the quality and shelf life of beef liver storage under refrigerated temperature (4°C). For this purpose, raw beef liver sample was divided into five treatments groups as T1 (day 1or control), T2 (day 2), T3 (day 3), T4 (day 4) and T5 (day 5). Sensory attributes, proximate composition, pH value, cooking loss, free fatty acids (FFA), peroxide value (POV) and microbial load such as total viable count (TVC), total coliform count (TCC) and total yeast mould count (TYMC) analysis were carried out for each treatment. The results show that color, odor, juiciness, and tenderness were significantly (P<0.05) decreased with increase the storage periods. Dry matter and ash contents were significantly (P<0.05) increased, whereas, crude protein and either extract were decreased with increase storage periods. Consequently, the cooking loss (%), FFA and POV values were significantly (P<0.05) increased, while pH value was significantly (P<0.05) decreased with the increase of storage periods. Moreover, TVC (log CFU/g), TCC (log CFU/g), and TYMC (log CFU/g) were also showed significantly (P<0.05) higher value for T3 and T5 compared to T1 . These findings suggest that shelf life of raw beef liver at refrigeration temperature (4°C) may be maximum three days with minor changes of quality.